Editorial for special issue: highly efficient energy harvesting based on nanomaterials - Lee, Seok Woo (2022)
Energy-harvesting systems generate electricity or produce fuels such as hydrogen from various energy sources such as thermal energy, kinetic energy, and renewable energy. For several decades, many researchers have studied the conversion of such energy for use in applications on various scales, from mega-watt grid systems to the micro-watt internet of things (IoTs). This Special Issue entitled “Highly Efficient Energy Harvesting Based on Nanomaterials” presents seven peer-reviewed journal papers written by outstanding authors worldwide [1,2,3,4,5,6,7]. These novel studies cover various topics related to thermal energy management, kinetic energy harvesting, and electrochemical energy conversion.